2001
DOI: 10.1046/j.1432-1327.2001.02384.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of biologically active glycoforms of bovine follicle stimulating hormone in plants

Abstract: We chose the follicle stimulating hormone (FSH), a pituitary heterodimeric glycoprotein hormone, as a model to assess the ability of the plant cell to express a recombinant protein that requires extensive N-glycosylation for subunit folding and assembly, intracellular trafficking, signal transduction and circulatory stability. A tobacco mosaic virus (TMV) based transient expression system was used to express a single-chain (sc) version of bovine FSH in the tobacco related species Nicotiana benthamiana. Prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…Plant RNA virus-based vectors, on the other hand, are rapidly amplified and produce large amounts of recombinant proteins, and in theory we can use any plant that can be infected by the viral vector. In fact, many foreign proteins have been successfully expressed using plant viral vectors (Dirnberger et al 2001;Pérez Filgueira et al 2003;Wagner et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Plant RNA virus-based vectors, on the other hand, are rapidly amplified and produce large amounts of recombinant proteins, and in theory we can use any plant that can be infected by the viral vector. In fact, many foreign proteins have been successfully expressed using plant viral vectors (Dirnberger et al 2001;Pérez Filgueira et al 2003;Wagner et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The b-a configuration was widely used to produce recombinant single-chain glycoprotein hormones of many species (Narayan et al 1995, Boime & BenMenahem 1999, Dirnberger et al 2001, Fidler et al 2003, Min et al 2004, Jablonka-Shariff et al 2007, sometimes with heterologous CTP from hCG inserted between fused a-and b-subunits to enhance the secretion of these single-chain protein variants (Sugahara et al 1996, Garcia-Campayo et al 1997, Grossmann et al 1997, Fares et al 1998. These earlier studies showed that the CTP played the role of a flexible hydrophilic spacer allowing genetically fused a-and b-subunits to adopt a functional conformation and that secretion in the presence of CTP was enhanced due to its specific O-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Most pharmaceutical proteins are glycoproteins; N-glycosylation of these proteins is essential for their solubility, stability, bioactivity, proper folding, and pharmacokinetics (Matsumoto et al, 1995;Dirnberger et al, 2001). Plants can perform N-glycosylation similar to mammals, which gives these plants a key advantage over other heterologous expression systems (Catherine Rayon, 1998;Lerouge et al, 1998).…”
Section: Introductionmentioning
confidence: 99%